Tumour cell-activated platelets modulate the immunological activity of CD4+, CD8+, and NK cells, which is efficiently antagonized by heparin - Gockel, Lukas M.; Nekipelov, Katrin; Ferro, Vito; Bendas, Gerd; Schlesinger, Martin (Cancer Immunology, Immunotherapy, 2022)
Platelets, key players in haemostasis, are progressively investigated with respect to their role in immunity and inflammation. Although the platelet support to haematogenous cancer cell metastasis has been the subject of multiple studies, their impact on anti-cancer immunity remains unaddressed. Here, we investigated the immunomodulatory potential of platelets upon their activation by MDA-MB-231 breast cancer cells in various in vitro approaches. We provide evidence that platelets as well as their tumour cell-induced releasates increased the ratio of regulatory T cells, shaping an immunosuppressive phenotype in isolated CD4 + cultures. The influence on CD8 + T cells was assessed by detecting the expression of activation markers CD25/CD69 and release of cytolytic and pro-inflammatory proteins. Notably, the platelet preparations differentially influenced CD8 + T cell activation, while platelets were found to inhibit the activation of CD8 + T cells, platelet releasates, in contrast, supported their activation. Furthermore, the NK cell cytolytic activity was attenuated by platelet releasates. Low molecular weight heparin (LMWH), the guideline-based anticoagulant for cancer-associated thrombotic events, is known to interfere with tumour cell-induced platelet activation. Thus, we aimed to investigate whether, unfractionated heparin, LMWH or novel synthetic heparin mimetics can also reverse the immunosuppressive platelet effects. The releasate-mediated alteration in immune cell activity was efficiently abrogated by heparin, while the synthetic heparin mimetics partly outperformed the commercial heparin derivatives. This is the first report on the effects of heparin on rebalancing immunosuppression in an oncological context emerging as a novel aspect in heparin anti-tumour activities.